Finite element analysis of electric motorcycle frame using SolidWorks: A comparative study of circular tube and square tube - Nicolus Obeth Theopilus Simanjuntak; Zeyar Min Thwin Htoo; Mukesh Singh (Journal of Engineering Researcher and Lecturer, 2023)
The frame is one of the critical components of a motorcycle. It needs to be robust, strong, and capable of withstanding various loads such as the engine, body, fuel tank, riders, passengers, and more. Apart from serving as a support for riders, passengers, and cargo, the frame also plays a vital role in connecting the front and rear suspension systems and linking the rear with the front wheel. This research aims to determine the strength of two material profiles, namely circular tube and square tube, in a comparison between AISI 1035 steel (SS) and AISI 1020 for the frame of an electric motorcycle. The comparison is analyzed through simulation results obtained using SolidWorks Research License 2021-2022 with the finite element method. The simulation results reveal that the most suitable profile and material for the frame, characterized by strength, durability, and load-bearing capacity, is the circular tube with AISI 1035 steel (SS). The data shows that the maximum stress occurring after applying the specified load remains within the yield strength of the material. Compared to other profiles and materials, this combination exhibits lower maximum stress, making it a superior choice. This study provides valuable insights into designing a motorcycle frame that can withstand various stresses while ensuring rider safety and optimal performance.